2016
DOI: 10.3389/fncom.2016.00109
|View full text |Cite
|
Sign up to set email alerts
|

Effective Suppression of Pathological Synchronization in Cortical Networks by Highly Heterogeneous Distribution of Inhibitory Connections

Abstract: Even without external random input, cortical networks in vivo sustain asynchronous irregular firing with low firing rate. In addition to detailed balance between excitatory and inhibitory activities, recent theoretical studies have revealed that another feature commonly observed in cortical networks, i.e., long-tailed distribution of excitatory synapses implying coexistence of many weak and a few extremely strong excitatory synapses, plays an essential role in realizing the self-sustained activity in recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In both cases, the synchronization index was kept within a low level ( SI < 0.05), indicating that asynchronous firings have been realized in this region. It has been shown by Kada et al (2016) that heterogeneity in the inhibitory-to-excitatory connections plays a key role in suppressing synchronized firing activities in a cortical network. The lognormal distribution, introduced to the inhibitory-to-excitatory connections, functioned efficiently to maintain the desynchronized firing dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, the synchronization index was kept within a low level ( SI < 0.05), indicating that asynchronous firings have been realized in this region. It has been shown by Kada et al (2016) that heterogeneity in the inhibitory-to-excitatory connections plays a key role in suppressing synchronized firing activities in a cortical network. The lognormal distribution, introduced to the inhibitory-to-excitatory connections, functioned efficiently to maintain the desynchronized firing dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that lognormal distribution of inhibitory-to-excitatory connections plays an important role of suppressing synchronized neuronal firings especially in a high-frequency firing state (Kada et al, 2016). This setting is consistent with the physiological experiments reporting that inhibitory postsynaptic potentials (IPSPs) are indeed highly heterogeneous in the cortex (Miles and Wong, 1984; Holmgren et al, 2003; Chapeton et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important research subject in neuroscience is to understand how cortical networks avoid or reach states of high synchronization (Kada et al, 2016). In normal activity, excitatory and inhibitory currents are well balanced (Tatti et al, 2018;Zhou and Yu, 2018), while in epileptic seizures, high synchronous behavior has been related to unbalanced current inputs (Drongelen et al, 2005;Avoli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported that excitatory synapses facilitate neural synchronization (Borges et al, 2017;Breakspear et al, 2003), while inhibitory synapses have an opposite effect (Kada et al, 2016;Ostojic, 2014;Protachevicz et al, 2019). The time delay related to excitatory and inhibitory synapses influences the neural synchronization (Gu and Zhou, 2015;Protachevicz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%